An Oxford SWIFT Integral Field Spectroscopy study of 14 early-type galaxies in the Coma cluster - Scott, N; Houghton, R; Davies, R; Cappellari, M; Thatte, N; Clarke, F; Tecza, M (2012)
As a demonstration of the capabilities of the new Oxford SWIFT integral field spectrograph, we present first observations for a set of 14 early-type galaxies in the core of the Coma cluster. Our data consist of I- and z-band spatially resolved spectroscopy obtained with the Oxford SWIFT spectrograph, combined with r-band photometry from the SDSS archive for 14 early- type galaxies. We derive spatially resolved kinematics for all objects from observations of the calcium triplet absorption features at \sim 8500 AA . Using this kinematic information we classify galaxies as either Fast Rotators or Slow Rotators. We compare the fraction of fast and slow rotators in our sample, representing the densest environment in the nearby Universe, to results from the ATLAS3D survey, finding the slow rotator fraction is \sim 50 per cent larger in the core of the Coma cluster than in the Virgo cluster or field, a 1.2 σ increase given our selection criteria. Comparing our sample to the Virgo cluster core only (which is 24 times less dense than the Coma core) we find no evidence of an increase in the slow rotator fraction. Combining measurements of the effective velocity dispersion {σ_e} with the photometric data we determine the Fundamental Plane for our sample of galaxies. We find the use of the average velocity dispersion within 1 effective radius, {σ_e}, reduces the residuals by 13 per cent with respect to comparable studies using central velocity dispersions, consistent with other recent integral field Fundamental Plane determinations.